The Effect Of Fertilizing Cabbage Waste Compost With Cow Dung on Cucumber Generative Growth (Cucumis sativus L. Varieties Hercules) - Dian Islamiati; Hafnati Rahmatan; Supriatno Supriatno; Muhibbudin Muhibbudin; Hasanuddin Hasanuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
This study aims to determine how the effect of composting cabbage waste with cow dung on the generative growth of cucumbers and knowing the composition of cabbage waste compost with cow dung which will give the best effect on cucumber generative growth. This study used an experimental method with a Completely Randomized Design (CRD) experiment with 4 treatments and 6 replications. The parameters of this study were plant length, leaf width, and number of leaves. Data were analyzed using Analysis of Variance Test (ANOVA) and further tests in the form of Least Significant Difference (BNT) and Duncan's Real Distance Test (JNTD) at the 95% confidence level. The results showed that the addition of cabbage waste compost with cow dung had a significant effect on increasing cucumber growth, and the best composition of cabbage waste compost with cow dung in increasing cucumber growth was P1 (50% cabbage waste compost + 50% cow dung).Keywords: cucumber, generative growth, cabbage waste compost Penelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh pemberian pupuk kompos limbah kol dengan kotoran sapi pada pertumbuhan generatif mentimun dan mengetahui komposisi pupuk kompos limbah kol dengan kotoran sapi yang akan memberikan pengaruh terbaik pada pertumbuhan generatif mentimun. Penelitian ini menggunakan metode eksperimen dengan percobaan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan dan 6 ulangan. Parameter penelitian ini adalah panjang tanaman, lebar daun, dan jumlah daun. Data dianalisis dengan menggunakan Uji Analisis Varian (ANAVA) dan uji lanjut berupa Beda Nyata Terkecil (BNT) dan Uji Jarak Nyata Duncan (JNTD) pada taraf kepercayaan 95%. Hasil penelitian menunjukkan bahwa pemberian pupuk kompos limbah kol dengan kotoran sapi berpengaruh nyata dalam meningkatkan pertumbuhan mentimun, dan komposisi pupuk kompos limbah kol dengan kotoran sapi yang paling baik dalam meningkatkan pertumbuhan mentimun adalah P1 (50% kompos limbah kol + 50% kotoran sapi).Kata kunci: mentimun, pertumbuhan generatif, kompos limbah kol.